Evaluation of Ligand-Inducible Expression Systems for Conditional Neuronal Manipulations of Sleep in Drosophila. Issue 10 (1st October 2016) - Li, Qiuling; Stavropoulos, Nicholas
Abstract: Drosophila melanogaster is a powerful model organism for dissecting the molecular mechanisms that regulate sleep, and numerous studies in the fly have identified genes that impact sleep–wake cycles. Conditional genetic analysis is essential to distinguish the mechanisms by which these genes impact sleep: some genes might exert their effects developmentally, for instance by directing the assembly of neuronal circuits that regulate sleep; other genes may regulate sleep in adulthood; and yet other genes might influence sleep by both developmental and adult mechanisms. Here we have assessed two ligand-inducible expression systems, Geneswitch and the Q-system, for conditional and neuronally restricted manipulations of sleep in Drosophila . While adult-specific induction of a neuronally expressed Geneswitch transgene ( elav-GS ) is compatible with studies of sleep as shown previously, developmental induction of elav-GS strongly and nonspecifically perturbs sleep in adults. The alterations of sleep in elav-GS animals occur at low doses of Geneswitch agonist and in the presence of transgenes unrelated to sleep, such as UAS-CD8-GFP . Furthermore, developmental elav-GS induction is toxic and reduces brood size, indicating multiple adverse effects of neuronal Geneswitch activation. In contrast, the transgenes and ligand of the Q-system do not significantly impact sleep–wake cycles when used for constitutive, developmental, or adult-specific neuronal induction. The nonspecific effects of developmental elav-GS activation on sleep indicate that such manipulations require cautious interpretation, and suggest that the Q-system or other strategies may be more suitable for conditional genetic analysis of sleep and other behaviors in Drosophila .